2017
DOI: 10.1002/jsfa.8298
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the phenolic compounds and antioxidant activities in germinated adlay seeds

Abstract: Germinated adlay had higher free and total phenolic and flavonoid contents, and antioxidant activities than ungerminated adlay. This study indicates that germinated adlay could be a promising functional food, more suitable for human consumption. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 29 publications
5
44
0
1
Order By: Relevance
“…During germination, the FRAP values of the adlay extracts increased in line with the TPC content ( r = 0.997), which is consistent with the observation made in our previous study (Xu et al ., ). The increases of TPC and FRAP of adlay water extracts were due to the better phenolic extractability and improved enzyme synthesis after germination (Chen et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…During germination, the FRAP values of the adlay extracts increased in line with the TPC content ( r = 0.997), which is consistent with the observation made in our previous study (Xu et al ., ). The increases of TPC and FRAP of adlay water extracts were due to the better phenolic extractability and improved enzyme synthesis after germination (Chen et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In our previous work, germination of adlay has been found to not only increase the contents of γ‐aminobutyric acid and coixol but also change the physicochemical properties (Xu et al ., ). Additionally, the germination process augmented the levels of phytochemicals (phenolic and flavonoid) and enhanced the antioxidant properties of adlay (Xu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The antioxidant activity is related to the potential of the compounds presented in a biological system to defend against the damaging effects of oxidative stress (Mendoza‐Sánchez et al, ). Antioxidant capacities have generally been suggested to be highly correlated with the contents of phytochemicals (phenolic and flavonoid compounds) (Xu, Wang, et al, ). The antioxidant activity of the adlay phenolic extract evaluated by the ORAC assay is presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the germination process can improve the contents of various biological compounds and reduce the levels of some antinutrition factors. Several studies have recently shown that germination changed the phenolic profiles and increased the total phenolic content (TPC) and antioxidant activities of cereals (Chen, Yu, Wang, Gu, & Beta, ; Xu, Wang, et al, ). During germination, the level of phytase activity increased, which caused a significant decrease in the content of the antinutrient phytate of some cereal grains, including rice, maize, millet, sorghum, and wheat (Azeke, Egielewa, Eigbogbo, & Ihimire, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation